Myelin‐Associated Glycoprotein is Altered in a Familial Late‐Onset Orthochromatic Leukodystrophy - Giordana, Maria Teresa (Brain Pathol, 2006)
Adult‐onset dominant leukodystrophies are a heterogeneous group of rare disorders, whose etiology, pathogenesis and molecular background are still unknown. We report the neuropathological and biochemical investigations of the brains and their myelin proteins components in 2 members of an Italian family affected by an adult‐onset autosomal dominant leukoencephalopathy. Clinical signs included spastic paraparesis, pseudobulbar syndrome, action tremor of head and hands, and moderate memory impairment. No mental deterioration or neuropathy was present. Onset was subacute (range 42–53 years) and progression spanned 4 to 7 years. The neuropathological phenotype overlapped that of orthochromatic leukodystrophies. The biochemical analysis revealed an abnormal myelin‐associated glycoprotein (MAG); the defect was localized at the C‐terminal domain of the L‐MAG isoform, resulting in a protein approximately 5 kDa shorter than the normal counterpart. No mutation in the MAG gene‐coding regions was uncovered, and linkage analysis formally excluded the entire MAG locus. We show that the identified MAG protein alteration is probably due to an abnormal post‐translational event. Considering MAG function in the maintenance of myelin, the abnormal protein may have a role in the pathogenesis of this disease. This is the first report of a possible pathogenetic role of MAG in a hereditary disease affecting the central white matter.